Roupa urbana, a moda e o grafite - Ribeiro, Tayná Brites (2017)
The purpose of this project is to refer to an urban art in a minimalist way through fashion. The result of the bibliographic research that described how this art began to be used as a way of expression. There is an explanation of the definition and styles of graffiti, its influence on fashion and how they correlate. The significance of the graffiti in the 1980s given the brand brings graffiti in a detailed way in cuts, colors and the fabrics textures turning away from the focus on prints. After raising these questions as a result of the exploratory research with bibliographical character, a brand that meets the segment of streetwear, referencing artists of the grafitti.